A Facile Synthesis of High‐Surface‐Area Sulfur–Carbon Composites for Li/S Batteries. Issue 28 (26th May 2015) - Kaiser, Mohammad Rejaul; Liang, Xin; Konstantinov, Konstantin; Liu, Hua‐Kun; Dou, Shi‐Xue; Wang, Jia‐Zhao
Abstract Small‐grained elemental sulfur is precipitated from sodium thiosulfate (Na2S2O3) in a carbon‐containing oxalic acid (HOOCCOOH) solution through a novel spray precipitation method. Surface area analysis, elemental mapping, and transmission electron micrographs revealed that the spray‐precipitated sulfur particles feature 11 times higher surface area compared to conventional precipitated sulfur, with homogeneous distribution in the carbon. Moreover, the scanning electron micrographs show that these high‐surface‐area sulfur particles are firmly adhered to and covered by carbon. This precipitated S–C composite exhibits high discharge capacity with about 75 % capacity retention. The initial discharge capacity was further improved to 1444 mA h g−1 by inserting a free‐standing single‐walled carbon nanotube layer in between the cathode and the separator. Moreover, with the help of the fixed capacity charging technique, 91.6 % capacity retention was achieved.